Answer:
Step-by-step explanation:
3(2x – 8)
3(2x) + 3(-8)
6x + -24
6x - 24
Hope this helps!
Answer:
b = -9
Step-by-step explanation:
1. Move the variables to the left side. Be sure to change the terms (add/subtract)
-9b-6 = -3b+48
-9b+3b-6 = 48
2. Combine like terms.
-9b+3b-6 = 48
-6b = 48 + 6
3. Divide both sides by -6.
-6b = 54
b = -9
Answer:
me espanol?
Step-by-step explanation:
Yes, since the other two numbers on each side are the same, any number can fit well in this equation.
Answer:
The answer to your question is See the attachment
Step-by-step explanation:
Equation
(x - 8)² + (y + 5)² = 4
Process
1.- Write the standard equation of the circle
(x - h)² + (y - k)² = r²
2.- Find the center
The center are the letters h and k
h = 8 k = -5
3.- Find the radius
r = 2
4.- Graph the circle ( i will use geogebra)
See below